Framing Issues of Ex-Prisoners, Vote Buying, and Winning Teams: Evidence from Pilkada of the Palangka Raya City - Anyualatha Haridison (Journal of Governance and Public Policy, 2021)
This manuscript specifically explores the dynamics of the Pilkada of Palangka Raya City in 2018. As with the simultaneous regional elections in Indonesia in general, there are still problems related to the practice of vote buying, network of winning teams and strong patronage. This is a determining factor in a candidate's victory, even though he was once labeled a prisoner. We observed a phenomenon in the Pilkada of Palangka Raya City; that having high popularity and strong political clientelism cannot help a person that is labeled an ex-prisoner to attain victory. Our study is complemented by a case study approach with a holistic analysis method. We observed and interviewed key informants in order to obtain some data related to the theme. Results show that the ability of the winning candidate’s team to frame and counter frame the candidate as an ex-prisoner  who gives cash to former fellow inmates, succeeded in helping the other candidate to win the Pilkada in the Palangka Raya City. We found that the implementation of the frame and counter frame theories was successful in the Pilkada context. This method of framing and counter framing is very effective in producing regional leaders with integrity and clean records and in instilling rationality in voters to reject corrupt leaders. Empirically, the limitations in framing these issues have not completely eliminated the pattern of giving money in politics.